Design Principles and Methodologies From Conceptualization to First Prototyping with Examples and Case Studies - Freddi, Alessandro; Salmon, Mario; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces readers to the core principles and methodologies of product development, and highlights the interactions between engineering design and industrial design. It shows to what extent the two cultures can be reconciled, and conversely what makes each of them unique. Although the semantic aspect is fundamental in industrial design, while the functional aspect is essential for the industrial product, the interaction between the two worlds is strategically vital. Design is also a strategic problem-solving process that drives innovation, builds business success and leads to better quality of life through innovative products, systems, services and experiences. The book connects product development with the concepts and strategies of innovation, recognizing that product design is a complex process in which invention, consumers' role, industrial technologies, economics and the social sciences converge. After presenting several examples of artifacts developed up to the conceptual phase or built as prototypes, the book provides a case study on a packaging machine, showcasing the principles that should underlie all design activities, and the methods that must be employed to successfully establish a design process. The book is primarily targeted at professionals in the industry, design engineers and industrial designers, as well as researchers and students in design schools, though it will also benefit any reader interested in product design. .
Introduction -- Engineering Design and Industrial Design -- Design Methods -- Requirements and Specications -- Invention and Innovation -- Safety Assessment -- Design of Experiment -- Introduction to the Taguchi Method -- One-off Product Design -- Design of a Packaging Machine: General Description and Conceptualization -- Embodiment Design of the Packaging Machine: Prototype Development.
Keywords: Engineering design; Technological innovations; Industrial engineering; Production engineering; Economic development; Consumer behavior; Engineering Design; Innovation and Technology Management; Industrial and Production Engineering; Economic Development, Innovation and Growth; Consumer Behavior